Infection with a novel polymycovirus enhances growth, conidiation and sensitivity to UV-B irradiation of the entomopathogenic fungus Metarhizium anisopliae - Wang, Ping; Yang, Guogen; Lu, Hanwen; Huang, Bo (Frontiers in Microbiology, 2023)
Metarhizium anisopliae is a well-studied entomopathogenic fungus that is widely used in biological control programs. The presence of polymycoviruses in this fungus is common, but their effects on fungal development and stress tolerance are not well understood. In this study, we report the discovery of a novel double-stranded RNA virus, named Metarhizium anisopliae polymycovirus 1 (MaPmV1), which comprises four dsRNAs ranging from 2.4 to 1.4 kbp in length. Phylogenetic analysis revealed that MaPmV1 belongs to the Polymycoviridae family. Biological comparison between MaPmV1-infected (Vi) and -free (Vf) isogenic lines showed that MaPmV1 remarkably enhances the growth rate and conidiation of the host fungus. The upregulation of growth-and conidiation-related genes in Vi strains supports this finding. In addition, MaPmV1 increases the sensitivity of the host to UV-B irradiation, which is evidenced by the downregulation of DNA damage repair genes in Vi strains. However, MaPmV1 does not appear to have any significant impact on the virulence of M. anisopliae. Furthermore, overexpression of individual viral proteins in M. anisopliae did not result in any significant phenotypic alterations, indicating that MaPmV1-mediated changes are not related to a single viral protein. Overall, our findings suggest that mycoviruses can be exploited to enhance fungal development in entomopathogenic fungi, which may lead to improved conidium production on a large scale.